Strategi dan Implementasi Komunikasi Pemerintah Surakarta dalam Edukasi Pencegahan Stunting (Studi Kasus Program “Sultanikah Capingan”) - Putra, Yon Setyaadi Ade (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2024)
Background. Stunting is one of the serious problems that must be prevented from the beginning through an effective health communication strategy as an effort to increase knowledge about stunting through education to the community. Objective. This study aims to determine the stages of the strategy carried out, communication actors, message content, and communication channels used as well as locality factors that shape the communication approach in the communication strategy carried out. Methods. This research uses an interpretive paradigm with a qualitative type. The method used is the case study method with data collection using interview techniques. Results. Target determination using situation analysis using only non-educational factors. The message delivered is a health communication message with family planning officers as communication actors. Message delivery uses participatory, psychological and cultural approaches through local languages to increase the effectiveness of message reception. In the implementation of communication strategies, there are still constraints on human resources as communication actors, which has an effect on the coverage of the number of audiences who have been successfully educated, which has a mutually sustainable effect in assisting at-risk families.